2018
DOI: 10.13189/fst.2018.060101
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition of Three Selected Traditional Diets: A Case Study of Ngwa People in Abia State, Nigeria

Abstract: The consumption and encouragement of indigenous diets could help alleviate malnutrition and mitigate food insecurity in developing countries. In this regard, three Nigerian traditional diets: Akidi (Vigna unguiculata), Akara-Igboro (manihot esculenta), and Ofe-achara (Pennisetum purpureum soup) mixed with Mgbam (baked melon seed) and Garri (Cassva flakes) were evaluated for sensory characteristics, proximate composition, anti-nutrient composition, as well as vitamins, and mineral content using standard methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Koodagi et al [21] have studied the macronutrient status of popular street foods in Karnataka. Amadi et al [22] have studied the nutritional composition of traditional dishes such as Kekefiyai, Kiri-igina, and Opuru-fulou of Bayelsa State, Nigeria. Israel and Samuel (2020) [23] have studied the proximate composition in eight street foods such as roasted plantain, fish, yam, corn and dough nuts, suya, eggroll, meat-pie from parts of Lagos Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Koodagi et al [21] have studied the macronutrient status of popular street foods in Karnataka. Amadi et al [22] have studied the nutritional composition of traditional dishes such as Kekefiyai, Kiri-igina, and Opuru-fulou of Bayelsa State, Nigeria. Israel and Samuel (2020) [23] have studied the proximate composition in eight street foods such as roasted plantain, fish, yam, corn and dough nuts, suya, eggroll, meat-pie from parts of Lagos Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…The seafood samples were also analysed for the presence of Na, K, Mg, Fe, and Mn, and the results obtained are presented in Table 3. The importance of minerals found in food materials to the body has been stressed [32,33]. Urga and Narasimha [34] observed that the nutritional value of diet in terms of elemental minerals is based on the amount of mineral that is available for physiological processes in the organism much more than the content in the diet.…”
Section: Metal Levels In the Seafood Samplesmentioning
confidence: 99%
“…A report on the micromineral content of 141 Nigerian foods [31] included only a few of the foods commonly consumed in Northern Nigeria. Limited data on indigenous meals are available for a few states including Jigawa in the north-west [32]; Nasarawa in the north-central [33]; Anambra, Enugu [34], and Abia [35] in the southeast; and Delta in the south-south of Nigeria [34]. In sum, a paucity of data exists on the nutrient profile of numerous foods included in traditional diets in the Bauchi State of Northeastern Nigeria.…”
Section: Introductionmentioning
confidence: 99%